THE ART OF SURVIVING THE TRAVEL BUSINESS DURING THE COVID-19 PANDEMIC - Mochammad Taufik Ramadhan Zain; Okky Rizal Ridwan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The COVID-19 pandemic has paralyzed all economic sectors, especially the tourism and travel business. Because this sector has close contact with humans and is completely contrary to government regulations during this pandemic. Therefore, companies need to issue management policies and strategies to maintain the continuity of this business. These policies and strategies include human resource management strategies, financial management, operational management, and business product innovation. This research was conducted on five tour and travel businesses in the city of Bandung. This research uses descriptive qualitative method. After researching, on average these five travelers implement new strategies, habits and innovations in their companies.Apart from that, it also discusses the marketing of the tour and travel business during the pandemic as well as in the future. The results of this study are that the five tour and travel businesses during this pandemic must continue to operate by implementing business strategies, marketing and also innovating with new types of tourism that have never been tried before, to make business turns that are not in line with their companies.